2012
DOI: 10.1088/1757-899x/33/1/012111
|View full text |Cite
|
Sign up to set email alerts
|

Phase-field modeling of the dendrite orientation transition in Al-Zn alloys

Abstract: With a few exceptions, phase-field simulations of dendritic growth in cubic materials have been modeled using simple expressions for the interfacial energy anisotropy and with strong anisotropy. However, recent experimental results show that the Dendrite Orientation Transition (DOT) observed in Al-Zn alloys by Gonzales and Rappaz [Met. Mat. Trans. A37 (2006) 2797] occurs at weak anisotropy, and modeling these results requires at least two anisotropy parameters. In the present work, we solve the corresponding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 22 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…This specific composition was selected because it has been shown to be the upper limit for which h1 0 0i dendrites are observed. Above this composition, the system exhibits a dendrite orientation transition (DOT), i.e., a gradual transition from h1 0 0i to h1 1 0i, which has been interpreted as a modification of the solid-liquid interfacial energy anisotropy [10,11,19]. In DS Al-20 wt.% Zn, we already found that minute additions of Cr (typically 200 to 1000 ppm) drastically modify the dendrite growth direction from h1 0 0i to h1 1 0i, but the reason in this case is less clear [20].…”
Section: Introductionmentioning
confidence: 99%
“…This specific composition was selected because it has been shown to be the upper limit for which h1 0 0i dendrites are observed. Above this composition, the system exhibits a dendrite orientation transition (DOT), i.e., a gradual transition from h1 0 0i to h1 1 0i, which has been interpreted as a modification of the solid-liquid interfacial energy anisotropy [10,11,19]. In DS Al-20 wt.% Zn, we already found that minute additions of Cr (typically 200 to 1000 ppm) drastically modify the dendrite growth direction from h1 0 0i to h1 1 0i, but the reason in this case is less clear [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, new findings show that the observed macroscopic texture did not necessarily correspond to the actual growth direction. The growth seems to operate by an alternating growth direction mechanism and could be linked to the competition between 100 and 110 characters, which was simulated using phase field under equiaxed growth conditions [4,14].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, various generalization schemes for high anisotropy have been developed. [103][104][105][106][107] A cusp interface energy model 108,109) has also been used to treat the facet and a high-anisotropy kinetic coefficient 110,111) has been modeled. Recently, dendrite growth simulations have been performed both in the 2D [112][113][114] and 3D 115,116) spaces for materials with the hexagonal close-packed structure, such as Mg alloys, which are the lightest metallic materials, and therefore, very important as future industrial materials.…”
Section: Interface Anisotropymentioning
confidence: 99%